Literature Review: The Relationship of Protein Intake on the Incident of Stunting in Children - Asrini Safitri; Rahmy Djamil; Alisiah Rezky Ariyani Amroe (Sean Institute, 2024)
Stunting is a growth and development disorder in children due to chronic malnutrition and recurrent infections, which is characterized by their length or height being below a Z-score of -2 SD. The number of children under five at risk of stunting in Indonesia is still around 4.7 million. Classification of Stunting according to the nutritional status of children, both boys and girls. The macronutrient intake that most influences the occurrence of stunting is protein intake. Protein deficiency in children can cause low growth and bone maturity, which can lead to various medical conditions, one of which is stunting. The research method for this journal was a Literature Review via Google Scholar, NCBI and sciencedirect.com using the keywords Stunting, Protein, Children, then a total of 9 articles that met the inclusion criteria were reviewed. This research concludes that there is a relationship between protein intake and the incidence of stunting. This is characterized by lower protein intake in children who are stunted compared to children who are not stunted.